2020
DOI: 10.33396/1728-0869-2020-5-50-56
|View full text |Cite
|
Sign up to set email alerts
|

Air Temperature and Ozone Concentration as Risk Factors for Life-Threatening Cardiovascular Conditions in Southern Russia

Abstract: Heat waves and increasing tropospheric ozone concentration accompanying global warming are recognized as risk factors for public health. The aim of the study was to assess the associations between atmospheric air temperature, ozone concentration as risk factors for life-threatening cardiovascular conditions in Southern Russia. Methods. An ecological study was performed. The number of ambulance calls (the monthly average for 2017 and daily for January, April, July and October) for acute cerebrovascular conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is proved by studies in Moscow during the heat wave of 2010, where increase in ambulance calls was demonstrated for stroke, hypotension, angina -up to 2.5 times, for pneumonia -up to five times, compared to the same period of 2009 [54]. In Simferopol, the frequency of emergency calls in July was associated with high temperatures and increased concentrations of ozone in the air [65]. Increase in cardiovascular exacerbations in some patients with cardiovascular diseases -hypertensive crisis for hospital patients and ambulance calls was shown for cold wave in Moscow in winter 2012-2013 [43].…”
Section: Ambulance Calls During Periods With Extreme Air Temperaturementioning
confidence: 93%
“…This is proved by studies in Moscow during the heat wave of 2010, where increase in ambulance calls was demonstrated for stroke, hypotension, angina -up to 2.5 times, for pneumonia -up to five times, compared to the same period of 2009 [54]. In Simferopol, the frequency of emergency calls in July was associated with high temperatures and increased concentrations of ozone in the air [65]. Increase in cardiovascular exacerbations in some patients with cardiovascular diseases -hypertensive crisis for hospital patients and ambulance calls was shown for cold wave in Moscow in winter 2012-2013 [43].…”
Section: Ambulance Calls During Periods With Extreme Air Temperaturementioning
confidence: 93%